TRAVEL MARKETING AND POPULAR PHOTOGRAPHY IN BRITAIN, 1888-1939 - Dominici, Sara. ([Place of publication not identified])
1 online resource
Keywords: This book explores how popular photography influenced the representation of travel in Britain in the period from the Kodak-led emergence of compact cameras in 1888, to 1939. The book examines the implications of people's increasing familiarity with the language and possibilities of photography on the representation of travel as educational concerns gave way to commercial imperatives. Sara Dominici takes as a touchstone the first fifty years of activity of the Polytechnic Touring Association (PTA), a London-based philanthropic-turned-commercial travel firm. As the book reveals, the relationship between popular photography and travel marketing was shaped by the different desires and expectations that consumers and institutions bestowed on photography: this was the struggle for the interpretation of the travel image.